EFEKTIVITAS MODEL PEMBELAJARAN PJBL BERBASIS STEAM DENGAN PENDEKATAN DEEP LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR REFLEKTIF PADA MATERI PENYAJIAN DATA DIAGRAM BATANG KELAS V - Rinda Agustin, Nova; Rosmiati, Rosmiati; Ladyawati, Erlin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of Project Based Learning (PjBL) integrated with the STEAM approach in improving students’ reflective thinking skills in elementary mathematics learning. Mathematics learning in elementary schools often emphasizes procedural understanding, causing students to struggle in developing deeper conceptual understanding and reflective thinking abilities. This research employed a quasi-experimental design involving fifth-grade students. Data were collected through pretest-posttest, observation, and student response questionnaires. The results showed that the implementation of PjBL with the STEAM approach significantly improved students' reflective thinking skills, as indicated by the increase in N-Gain scores and positive student responses. The findings suggest that integrating PjBL and STEAM provides meaningful learning experiences and enhances students' higher-order thinking skills.